Over the river and through the wood : the New England boy's song about Thanksgiving day - Child, Lydia Maria, 1802-1880. (Somerville, Mass. : Candlewick Press, 2011)
An illustrated version of the poem that became a well- known song about a journey through the snow to grandfather's house for Thanksgiving dinner.
Keywords: Thanksgiving Day -- Juvenile poetry; Children's poetry, American; Children's songs -- Texts